Motivation and constraints of illocution in the Lexical Constructional Model. The case of the Aux NP construction. - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Nuria del Campo Martínez Universidad de La Rioja, Spain   ABSTRACT This article addresses the motivation and constraints of illocutionary meaning production. Within the framework of the Lexical Constructional Model (LCM), I explore how our knowledge of illocution is understood in terms of high-level situational models which are activated to produce speech act meaning and the way such operations motivate the conventionalized value of linguistic expressions. In so doing, I analyze the realization procedures of the Aux NP construction in relation to their potential to exploit the semantic base of requestive acts. I will study the most conventional linguistic realizations of the construction and explore the way in which such realizations are used to produce a requestive meaning. The resulting account provides a comprehensive understanding of the constructional nature of illocutionary meaning on the basis of naturally occurring data.